Weekly lifestyle counselling improves glucose level in type 2 diabetes mellitus patients - Amallia Nuggetsiana Setyawati; Inggar Octa Pusthika; Kusmiyati Tjahjono DK (Faculty of Medicine, Universitas Trisakti, 2013)
INTRODUCTIONRegular physical exercise and healthy life style have been demonstrated to improve health status of a number of populations. In adherence, counselling on life style and dietary nutrition have been one of the investigated methods todetermine its effectiveness toward metabolic syndrome predictors. The aim of this study was to evaluate the effect of lifestyle change and dietary counselling on glucose level, body mass index (BMI), waist circumference, blood pressure,total cholesterol, triglycerides, low density lipoprotein (LDL), and high density lipoprotein (HDL) in type 2 diabetes mellitus (T2DM) patients.METHODSA randomized controlled trial was conducted and 26 diagnosed subjects with T2DM were enrolled in the study. After initial screening, they were randomized into the control group and the intervention group, following stratification by gender and age. The intervention group received weekly counselling andeducation, while the control group received counselling and education only once at the initial meeting. Independent t-test was used to compare the glucose level between the two-groups.RESULTSLifestyle counselling and dietary modification effected a significant improvement in blood glucose (p=0.002), but not in BMI, waist circumference, total cholesterol, triglycerides, LDL and HDL. In addition, a positive time effect was found in theintervention group before and after treatment on BMI (p=0.009), waist circumference (p=0.0014), and glucose level (p=0.001). The intervention group also showed a significant positive attitude; almost all of the respondents tried to control their food intake and perform exercise regulary.CONCLUSIONDietary nutrition and lifestyle counselling improve blood glucose control in the short term.